Formulation strategies of probiotics in broilers: systematic review and meta-analysis of their effects on production performance - Opazo, Rafael; Salinas, Catalina; Villasante, Alejandro (Frontiers in Animal Science, 2025)
IntroductionThe broiler chicken industry has grown rapidly, suggesting that this sector plays a key role in ensuring global food security. However, to meet future needs, how chickens are raised must be improved, as probiotics are promising feed additives.MethodsWe conducted a systematic review of 338 articles retrieved from four scientific databases to evaluate the effectiveness of different probiotic formulations in broiler chickens. The analysis focused on body weight gain (BWG) and feed conversion ratio (FCR).ResultsThe most common probiotics were Bacillus, Lactobacillus, and a mixture of different genera types (Probiotic Mix). The results showed that these probiotic formulations had a significant positive effect on both BWG and FCR. The combined effect sizes for BWG were as follows: Lactobacillus (1.08); Probiotic Mix (0.96); and Bacillus (0.87). The effect sizes for FCR were as follows: Probiotic Mix (-1.32) Lactobacillus, (-1.22); and Bacillus (-1.04). Except for BWG in Bacillus category, there was considerable variation in the results. Researchers have also looked at factors such as probiotic dose (CFU/kg) and the number of strains in the Probiotic Mix, but these did not have a significant influence on heterogeneity. When converted combined effect sizes to metric units (g or kg), Lactobacillus showed the best results, with a 221.69 (g) increase in BWG and 0.17 (kg) decrease in FCR. ConclusionThis study demonstrates that probiotic supplementation, particularly Lactobacillus, improves growth performance and feed efficiency in broiler chickens. These findings support the inclusion of probiotics in poultry farming as a strategy to enhance production efficiency and contribute to future global food security.